Peripartum fetal Doppler sonography and perinatal outcome: a systematic review and meta-analysis - Bram Packet; Ann-Sophie Page; Jan Bosteels; Jute Richter (BMC Pregnancy and Childbirth)
Abstract Objective Systematically review and critically appraise the literature on the association between peripartum fetal Doppler sonography findings, i.e., acquired upon admission for spontaneous or induced labor, and perinatal outcome in term (37-42w) pregnancies. Methods Medline, Embase, Web of Science, Cochrane Library, and clinicaltrials.gov databases were systematically searched from inception to 05/2024. Studies conducted in unselected populations of term (37-42w) pregnancies, admitted for spontaneous or induced labor, reporting the association between fetal Doppler findings and perinatal outcome, were eligible for inclusion. Study eligibility was assessed independently by two reviewers. Methodological quality was assessed using the Quality In Prognosis Studies (QUIPS)-tool. Effect estimates were pooled using random-effects meta-analyses. Summary Odds Ratios (ORs) and Mean Differences (MDs) are reported with 95% confidence intervals. Results Thirty-seven studies, reporting on 11.505 women and neonates, were included. Fourteen studies reported on findings from the umbilical artery (UA), four on the middle cerebral artery (MCA), five on the umbilical vein (UV), and nine on the cerebroplacental ratio (CPR). An abnormal UA Doppler and CPR increased the odds of fetal distress (FD) during labor (UA: OR 3.67 [1.14, 11.78], I2 = 72% – CPR: OR 3.19 [2.68, 3.80], I2 = 0%) and subsequent operative delivery (ODFD) (UA: OR 3.65 [1.66, 8.04], I2 = 81% – CPR: OR 2.48 [1.66, 3.70], I2 = 57%). Likewise, the presence of UV pulsations was strongly associated with both outcomes (FD: OR 28.78 [11.21, 73.87], I2 = 0% – ODFD: OR 303.36 [11.11, 8279.82], I2 = 0%). Regarding neonatal outcome, an Apgar-score < 7 at 5 min and NICU admission occurred more frequently if Doppler findings were abnormal in the UA (Apgar: OR 3.65 [1.82, 7.34], I2 = 0% – NICU: OR 3.92 [2.36, 6.51], I2 = 0%), or in case of an abnormal CPR (Apgar: OR 3.64 [2.03, 6.54], I2 = 0% – NICU: OR 2.71 [1.15, 6.38], I2 = 0%). Neonatal birthweight was also lower in the presence of an abnormal UA or CPR result, with a MD of -630.61g ([-1234.29, -26.93], I2 = 80%) and -146.52g ([-285.03, -8.01], I2 = 0%) respectively. Most studies (70.3%) were at high risk of bias on one or more domains; only 11 studies had an overall low risk of bias score. Conclusion Doppler sonography in the peripartum period allows for the identification of fetuses at risk of adverse birth outcomes. Further research on optimal thresholds to define at-risk cases and subsequent management strategies is needed. PROSPERO registration number CRD42023413264.